Perancangan Aplikasi Kode Etik Profesi Dengan Menerapkan Algoritma Raita - Yulytawaty Napitupulu (STMIK Budi Darma, 2021)
Professional Code of Ethics is an ethical order that has been agreed upon by a certain community group. It can also be interpreted as a pattern of rules, procedures, signs, ethical guidelines in carrying out an activity or work. But in fact many professional actors do not know or care about the code of ethics of their own profession. The problem that occurs is that the professional code of ethics is generally written in a code of ethics book which is difficult to carry everywhere when compared to other books that are already application-based, either web-based or mobile-based. For this reason, with the application of this professional code of ethics, professional actors and the entire community can easily find out the desired professional code of ethics by searching for a professional code of ethics that has been determined according to the existing pattern. This professional code of ethics search application is designed using the string matching method. Application development uses the Unified Modeling Language (UML) planning method and is built on the android platform.